Financial Distress In Diverse Industry Contexts: A Comprehensive Systematic Literature Review - Carolina Ety Widjayanti; Sri Lestari; Dian Purnomo Jati (International Journal of Economics, Business and Innovation Research, 2024)
Financial distress is a critical state affecting businesses across various industry contexts, characterized by significant challenges in meeting financial obligations and maintaining economic stability. This comprehensive systematic literature review (SLR) aims to provide a holistic understanding of financial distress in diverse industry settings, drawing insights from 25 articles published in Scopus-indexed journals between 2018 and 2023. The review identifies key factors contributing to financial distress, explores its impact on business performance and continuity, and discusses the development of predictive models. The findings highlight the importance of financial ratios, regulatory frameworks, risk management practices, and consumer behavior in understanding financial distress. Additionally, this review addresses crucial research questions related to publication trends, significant articles and journals, key contributors, and future research directions. The study emphasizes the need for advanced predictive models and comprehensive regulatory policies to mitigate financial distress and enhance economic resilience